The role of SERCA2a/PLN complex, Ca(2+) homeostasis, and anti-apoptotic proteins in determining cell fate - Vafiadaki, E.; Papalouka, V.; Arvanitis, DA; Kranias, EG; Sanoudou, D. (Pflugers ArchPflugers ArchPflugers Arch, 2009)
Intracellular calcium is a major coordinator of numerous aspects of cellular physiology, including muscle contractility and cell survival. In cardiac muscle, aberrant Ca(2+) cycling has been implicated in a range of pathological conditions including cardiomyopathies and heart failure. The sarco(endo)plasmic reticulum Ca(2+) transport adenosine triphosphatase (SERCA2a) and its regulator phospholamban (PLN) have a central role in modulating Ca(2+) homeostasis and, therefore, cardiac function. Herein, we discuss the mechanisms through which SERCA2a and PLN control cardiomyocyte function in health and disease. Emphasis is placed on our newly identified PLN-binding partner HS-1-associated protein X-1 (HAX-1), which has an anti-apoptotic function and presents with numerous similarities to Bcl-2. Recent evidence indicates that proteins of the Bcl-2 family can influence ER Ca(2+) content, a critical determinant of cellular sensitivity to apoptosis. The discovery of the PLN/HAX-1 interaction therefore unveils an important new link between Ca(2+) homeostasis and cell survival, with significant therapeutic potential.
Vafiadaki, ElizabethPapalouka, VasilikiArvanitis, Demetrios AKranias, Evangelia GSanoudou, DespinaengHL26057/HL/NHLBI NIH HHS/HL64018/HL/NHLBI NIH HHS/HL77101/HL/NHLBI NIH HHS/Research Support, N.I.H., ExtramuralResearch Support, Non-U.S. Gov'tReviewGermany2008/04/17 09:00Pflugers Arch. 2009 Jan;457(3):687-700. doi: 10.1007/s00424-008-0506-5. Epub 2008 Apr 16.
Keywords: *Homeostasis; Adaptor Proteins, Signal Transducing; Animals; Animals, Genetically Modified; Apoptosis Regulatory Proteins/*metabolism; Calcium-Binding Proteins/*metabolism; Calcium/*metabolism; Heart Failure/metabolism; Humans; Multiprotein Complexes/*metabolism; Myocytes, Cardiac/metabolism; Proteins/metabolism; Proto-Oncogene Proteins c-bcl-2/metabolism; Sarcoplasmic Reticulum Calcium-Transporting ATPases/*metabolism; Sarcoplasmic Reticulum/metabolism